Screening tools for oropharyngeal dysphagia in stroke - Tatiana Magalhães de Almeida (Audiology - Communication Research, 2015)
Purpose: To identify the parameters present in the screening tools for oropharyngeal dysphagia in stroke published in the literature. Research strategy: For the selection of studies, the swallowing disorder descriptors stroke, screening, evaluation and dysphagia were used. MEDLINE, Embase, LILACS, SciELO and the Cochrane Library databases were consulted. Selection criteria: We selected articles in the English, Portuguese and Spanish languages published up to December 2014 whose methodological approach referred to screening tools for oropharyngeal dysphagia designed for adults with stroke. The parameters used in the various screening tools were grouped by equality and/or likeness. We performed a descriptive analysis and calculated the frequency of found parameters. Results: We found 688 articles and after consideration of the inclusion and exclusion criteria, 23 articles were effectively analyzed. Of the 20 tools found, 90% used some type of food offer orally in screening for dysphagia, mostly water. We found 19 different parameters not related to food offer and 12 parameters related to food offer. Conclusion: There is no consensus among the studies on the most sensitive and specific parameters to compose the screening method for oropharyngeal dysphagia in stroke.